'A Victorian community overseas' transformed: demographic and morphological change in suburban Melbourne, Australia, 1947–1981. (August 2015) - O'HANLON, SEAMUS
ABSTRACT One of the world's great Victorian-era suburban metropolises, Melbourne, Australia, was transformed by mass immigration and the redevelopment of some of its older suburbs with low-rise flats and apartments in the post-war years. Drawing on a range of sources, including census material, municipal rate and valuation books, immigration and company records, as well as building industry publications, this article charts demographic and morphological change across the Melbourne metropolitan area and in two particular suburbs in the mid- to late twentieth century. In doing so, it both responds to McManus and Ethington's recent call for more histories of suburbs in transition, and seeks to embed the role of immigration and immigrants into Melbourne's urban historiography.